Effect of multimorbidity on hypertension management - Eunjeong Ji; Soyeon Ahn; Jung-Yeon Choi; Cheol-Ho Kim; Kwang-il Kim (Scientific Reports, 2023)
Abstract Multimorbidity, the coexistence of multiple health conditions, is associated with functional decline, disability, and mortality. We aimed to investigate the effects of multimorbidity on hypertension treatment and control rates by analyzing data from the Korean National Health and Nutrition Examination Survey database, which is a cross-sectional, nationally representative survey conducted by the Korean government. Multimorbidity, defined as having two or more chronic diseases, was evaluated by blood pressure measurements, blood chemistry examinations, and questionnaires. We classified the participants according to the number of multimorbidities from 0 to ≥ 6. Association analysis was performed to identify the patterns of multimorbidity related to hypertension control. From 2016 to 2020, 30,271 adults (≥ 20 years) were included in the analysis (age: 52.1 ± 16.8 years, male: 44.0%), and 14,278 (47.2%) had multimorbidity. The number of chronic conditions was significantly higher in older adults, women, and hypertensive patients. Multimorbidity was associated with hypertension treatment. The number of chronic conditions was significantly higher in controlled compared to uncontrolled patients (3.6 ± 1.7 vs 2.9 ± 1.6, p < 0.001). But the control rate of hypertension among treated patients was lower in patients with multimorbidity (75.6% in hypertension only group vs 71.8% in multimorbidity group, p = 0.009). Multimorbidity patterns showed distinct features in treated and controlled hypertensive patients. In conclusion, multimorbidity has a beneficial effect on the treatment of hypertension, but the control rate of systolic blood pressure was lower among the patients with multimorbidity. More attention should be paid to the hypertensive patients with multimorbidity to improve the control rate of hypertension.